2017
DOI: 10.1186/s12880-016-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET using SUVmax for preoperative T-staging of esophageal squamous cell carcinoma with and without neoadjuvant chemoradiotherapy

Abstract: BackgroundAccurate T-staging is pivotal for predicting prognosis and selecting appropriate therapies for esophageal squamous cell carcinoma (ESCC). The diagnostic performance of fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for its T-staging is uncertain. We investigated use of FDG PET/CT for preoperative T-staging of patients with ESCC.MethodsPatients with ESCC given preoperative FDG PET/CT scans, either with (CRT[+] group) or without (CRT[−] group) neoadjuvant chemoradiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 35 publications
(38 reference statements)
2
29
1
Order By: Relevance
“…Among the parameters tested for classification in our study, Entropy was ranked the most important by the algorithm. Entropy and Entropy-related features, which express disorder and heterogeneity of the image and -by extension- are hypothesized to mirror tumoral heterogeneity itself, have been demonstrated in (meta-)analyses of several different tumor entities and across imaging modalities as reliable and repeatable quantitative parameters [2426].…”
Section: Discussionmentioning
confidence: 99%
“…Among the parameters tested for classification in our study, Entropy was ranked the most important by the algorithm. Entropy and Entropy-related features, which express disorder and heterogeneity of the image and -by extension- are hypothesized to mirror tumoral heterogeneity itself, have been demonstrated in (meta-)analyses of several different tumor entities and across imaging modalities as reliable and repeatable quantitative parameters [2426].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to lymph nodes, reduction in the short axis of lymph nodes to <10 mm on chest CT and EUS was documented. In addition, there was no increased uptake of 18 F-fluorodeoxyglucose in PET scans with maximum standardized uptake values of >3.4 and >4.1 for primary esophageal tumor and lymph nodes, respectively [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…A small study ( n = 22) that was done on junior doctors to identify general pathologies on chest X-ray found a low overall accuracy and confidence (51 and 57.5%, respectively) (14). Another small study from Iran showed a low accuracy that reached only 8% for ARDS and 15% for normal chest X-ray among practitioners, pointing to the need for improving their emergency radiology curricula [ 9 ]. A recent study that included radiology residents showed that they generally have around 90.4 and 79.6% accuracy in identifying abnormal and normal chest X-rays, respectively, but only 52.7% in reaching the exact diagnosis, where they were tested on imagings of both life-threatening and non-life-threatening conditions [ 8 ].…”
Section: Discussionmentioning
confidence: 99%